Not-Sew-Wicked Stepmom. 4 - Iru (Graphic novelist); Mo9Rang (Graphic novel illustrator) (Ize Press, 2024)
"Once upon a time, a strange epidemic ravaged the land--including the halls of the royal palace! With Queen Abigail's birthday coming up, Sabrian and Blanche insist on a grand, four-day affair! Although Abigail initially declines, she can't deny that it might completely lay to rest any rumors of discord in her marriage. However, when a sudden outbreak of an unidentifiable illness threatens to ruin the festivities and even leaves the princess bedridden, Abigail takes matters into her own hands. Will she be able to find the cause of the mysterious plague in time?"--from back cover.